Diallyl trisulfide suppresses tumor growth through the attenuation of Nrf2/Akt and activation of p38/ JNK and potentiates cisplatin efficacy in gastric cancer treatment - Jiang, Xiao-yan; Zhu, Xiao-song; Xu, Hong-ya; Zhao, Zhong-xi; Li, Si-ying; Li, Shan-zhong; Cai, Jian-hua; Cao, Ji-min (Acta pharmacologica Sinica, 2017)
Diallyl trisulfide （DATS）, a garlic organosulfide, has shown excellent chemopreventive potential. Cisplatin （DDP） is widely used to treat solid malignant tumors, but causing serious side effects. In the current study, we attempted to elucidate the chemopreventive mechanisms of DATS in human gastric cancer BGC-823 cells in vitro, and to investigate whether DATS could enhance the anti-tumor efficacy of DDP and improve quality of life in BGC-823 xenograft mice in vivo. Treatment with DATS （25-400 pmol/L） dose-dependently inhibited the viability of BGC-823 cells in vitro with an IC5o of 115.2＋4.3 pmol/L after 24 h drug exposure. DATS （50-200 pmol/L） induced cell cycle arrest at G2/M phase in BGC-823 cells, which correlated with significant accumulation of cyclin A2 and B1. DATS also induced BGC-823 cell apoptosis, which was accompanied by the modulation of Bcl-2 family members and caspase cascade activation. In BGC-823 xenograft mice, administration of DATS （20-40 mg.kg-1.d-1, ip） dose-dependently inhibited tumor growth and markedly reduced the number of Ki-67 positive cells in tumors. Interestingly, combined administration of DATS （30 mg.kg-1.d-1, ip） with DDP （5 mg/kg, every 5 d, ip） exhibited enhanced anti-tumor activity with fewer side effects. We showed that treatment of BGC-823 cells with DATS in vitro and in vivo significantly activated kinases such as p38 and JNK/MAPK and attenuated the Nrf2/Akt pathway. This study provides evidence that DATS exerts anticancer effects and enhances the antitumor efficacy of DDP, making it a novel candidate for adjuvant therapy for gastric cancer.